Characteristics of fine particle matter at the top of Shanghai Tower - C. Yin; J. Xu; W. Gao; L. Pan; Y. Gu; Q. Fu; F. Yang (Atmospheric Chemistry and Physics, 2023)
To investigate the physical and chemical processes of fine particle matter (PM) at the mid-upper planetary boundary layer (PBL), we conducted 1-year continuous measurements of fine PM, the chemical composition of non-refractory submicron aerosol (NR-PM1), and some gas species (including sulfur dioxide, nitrogen oxides, and ozone) at an opening observatory (∼ 600 m) at the top of Shanghai Tower (SHT), which is China's first and the world's second highest building located in the typical financial central business district of Shanghai, China. This is the first report on the characteristics of fine particles based on continuous and sophisticated online measurements at the mid-upper level of the urban PBL. The observed PM2.5 and PM1 mass concentrations at SHT were 25.5 ± 17.7 and 17.3 ± 11.7 µg m−3, respectively. Organics, nitrate (NO3), and sulfate (SO4) occupied the first three leading contributions to NR-PM1 at SHT, accounting for 35.8 %, 28.6 %, and 20.8 %, respectively. The lower PM2.5 concentration was observed at SHT by 16.4 % compared with that near the surface during the observation period. It was attributed to the decreased nighttime PM2.5 concentrations (29.4 % lower than the surface) at SHT in all seasons due to the complete isolations from both emissions and gas precursors near the surface. However, daytime PM2.5 concentrations at SHT were 12.4 %–35.1 % higher than those near the surface from June to October, resulted from unexpected larger PM2.5 levels during early to middle afternoon at SHT than at the surface. We suppose the significant chemical production of secondary aerosols existed in the mid-upper PBL, because strong solar irradiance, adequate gas precursors (e.g., NOx), and lower temperature were observed at SHT, favorable for both photochemical production and gas-to-particle partitioning. This was further demonstrated by the significant increasing rate of oxygenated organic aerosols and NO3 observed at SHT during 08:00–12:00 in spring (7.4 % h−1 and 12.9 % h−1), fall (9.3 % h−1 and 9.1 % h−1), and summer (13.0 % h−1 and 11.4 % h−1), which cannot be fully explained by vertical mixing. It was noted that extremely high NO3 was observed at SHT both in daytime and nighttime in winter, accounting for 37.2 % in NR-PM1, suggesting the efficient pathway from heterogeneous and gas oxidation formation. Therefore, we highlight the priority of NOx reduction in Shanghai for the further improvement of air quality. This study reported greater daytime PM2.5 concentrations at the height of 600 m in the urban PBL compared with surface measurement, providing insight into their potential effects on local air quality, radiation forcing, and cloud and/or fog formations. We propose that the efficient production of secondary aerosol in the mid-upper PBL should be cognized and explored more comprehensively by synergetic observations in future.